1-D HEC-RAS modelling and the vulnerability level assessment of Belik River sub-watershed. Issue 1 (April 2021) - Prastica, R M S
Abstract: Restoration of sub-watershed needs a comprehensive point of views because the climate change factors could affect any environment aspects inside it. The paper investigates the Belik River sub-watershed in Yogyakarta, Indonesia. The research aims to analyze the characteristics of the river in the study area and to assess its vulnerability level. The observation employs HEC-RAS supporting tool to simulate 1-D frames of the river to visualize the characteristics of the river. Then, the vulnerability level is evaluated by field survey to conclude the restoration strategy in the sub-watershed. There are two findings in this research: first, the river has a high level of vulnerability to the water-related disaster and second, the sub-watershed is classified as high-risk level of the endangered environment. Hence, the proposed restoration strategy is compulsorily needed to mitigate and to rehabilitate the sub-watershed. To conclude, the Belik River sub-watershed could be categorized as a red zone of high-risk level towards environmental vulnerability to flooding, contaminants, aquatic habitat, and social prosperity.